Relationship Between Health-Related Quality of Life (HRQoL) Factors in Patients With Diabetes Mellitus : A Literature Review - Satyafebrianti, Kendra Callista; Santoso, Aktaruddin Arief (Journal of Diverse Medical Research: Medicosphere, 2025)
Background: Diabetes mellitus (DM) is a chronic disease that can significantly affect the quality of life of patients. Poor quality of life is often associated with poor disease control, complications, and psychosocial burden. A better understanding of the factors that affect the quality of life of DM patients is essential for designing effective interventions. Objective: This study aims to analyze the relationship between health-based quality of life factors and the condition of diabetes mellitus patients. Method: This study used a literature review method. Researchers collect data through database sources, such as PubMed, Google Scholar, and ScienceDirect. The articles used are in English. The keywords used in the article search are: "heart related quality of life" and "diabetes mellitus". The article search is limited to publications in the last 5 years (2019 to 2024). Results: The results showed that factors such as glycemic control, severity of complications, social support, and depression were significantly associated with the quality of life of patients. Patients with better glycemic control and higher social support reported better quality of life. Conclusion: Overall, the quality of life of diabetes mellitus patients is greatly influenced by various factors, including glycemic control, complications, social support, and psychosocial factors. To improve the quality of life of diabetes patients, it is important to provide a holistic approach that includes good medical management, emotional support, and social interventions that can improve their well-being.